A Brief Study about Rationality and Institutions - Jan-Erik Lane (Research Aspects in Arts and Social Studies Vol. 2, 2022)
In the social sciences, giving up on rational conduct has become normal. It is argued that rationality as the maximisation of self-interest is both impractical and morally wrong. However, the most crucial paradigm for comprehending human behaviour is rational choice. In his contribution to the study of human behaviour, D. Kahneman criticised the two extremes of perfect individual rationality and group or collective decision-making. The first suffers from bias and the second from noise. Thus, there is somewhat of a contradiction here somewhere, as group ratio- nality could not cancel out individual deficiencies. It is helpful to think of rationality as an ideal kind that can be used to examine actual behaviour. Informally, one can use Weber’s action frame of reference or expected value maximisation with game theory. In addition to intention, there must be a causal link between the actual means employed and the actual achievement of the aim.